Enhanced oil recovery mechanism and recovery performance of micro‐gel particle suspensions by microfluidic experiments. Issue 4 (2nd December 2019) - Lei, Wenhai; Liu, Tong; Xie, Chiyu; Yang, Haien; Wu, Tianjiang; Wang, Moran
Abstract: Micro‐gel particle suspensions (MGPS) have been proposed for enhanced oil recovery (EOR) in reservoirs with harsh conditions in recent years, yet the mechanisms are still not clear because of the complex property of MGPS and the complex geometry of rocks. In this paper, the micro‐gel particle‐based flooding has been studied by our microfluidic experiments on both bi‐permeability micromodels and reservoir‐on‐a‐chip. A method for reservoir‐on‐a‐chip design has been proposed based on QSGS (quartet structure generation set) to ensure that the flow geometry on chip owns the most important statistical features of real rock microstructures. In the micromodel experiments with heterogeneous microstructures, even if the MGPS has the same macroscopic rheology as the hydrolyzed polyacrylamides (HPAM) solution for flooding, MGPS may lead to significant fluctuations of pressure field caused by the nonuniform concentration distribution of particles. In the reservoir‐on‐a‐chip experiments, clustered oil trapped in the swept pores can be recovered by MGPS because of pressure fluctuation, which hardly happens in the HPAM flooding. Compared with the water flooding, the HPAM solution flooding leads to approximately 17% incremental oil recovery, while the MGPS results in approximately 49.8% incremental oil recovery in the laboratory. Abstract : The road map of reservoir‐on‐a‐chip design.